HUBUNGAN ANTARA USIA IBU HAMIL DENGAN KEJADIAN INFEKSI SALURAN KEMIH PADA IBU HAMIL DI RSUD DR. H. ABDUL MOELOEK BANDAR LAMPUNG TAHUN 2024 - Ida Laila; Sutarto; Muhammad Aditya; Hendra Tarigan Sibero (PT. Hasba Edukasi Mandiri, 2026)
Urinary Tract Infection (UTI) is one of the common complications during pregnancy and may cause serious adverse outcomes for both the mother and the fetus. Maternal age is recognized as a biological risk factor associated with the occurrence of UTI due to physiological and immunological changes during pregnancy. This study aimed to determine the association between maternal age and the incidence of urinary tract infection among pregnant women at RSUD Dr. H. Abdul Moeloek Bandar Lampung in 2024. This study employed an observational analytic design with a case-control approach. The study sample consisted of 52 pregnant women, comprising 26 pregnant women with UTI as the case group and 26 pregnant women without UTI as the control group. Data were obtained from medical records and questionnaires. Bivariate analysis was performed using the Fisher Exact test with a significance level of p < 0.05. The results showed a statistically significant association between maternal age and the incidence of UTI (p = 0.011; OR = 4.545; 95% CI: 1.370–15.077). In conclusion, there is a significant association between maternal age and the occurrence of urinary tract infection among pregnant women.